Clinico histopathological evaluation of abnormal uterine bleeding in women of reproductive and perimenopausal age group - jha, Ela; Jha, Arun Kumar; Samuel, Annie (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Abnormal uterine bleeding constitutes a significant proportion of cases attending gynaecology outpatient department. It affects woman’s physical, emotional, social and maternal well-being, and hence it demands adequate management. It is a multifactorial entity; presented in various patterns, signs and symptoms. The PALM COEIN classification is the most recent method of categorizing AUB (abnormal uterine bleeding) based on structural and non-structural causes. The treatment of AUB depends on age, parity, symptom severity, investigation findings and cause. Various invasive and non-invasive investigations including USG, endometrial biopsy and hysteroscopy helps find different causes. Whatever be the etiology endometrium gets affected; hence AUB is likely managed through hormonal preparations, LNG-IUS, endometrium ablation/resection and ultimately hysterectomy as the last resort. Methods: A retrospective study comprising 216 patients in the age group of 30-50 years with complaints of AUB were recorded as per a structured proforma at department of obstetrics and gynaecology, MGM MCH over a period of one year (January 2018-19). The results of investigations, ultrasound scans, endometrial biopsy and histopathology of hysterectomised specimens were correlated. The endometrial biopsy and histopathology of the specimens was done at department of pathology, MGM MCH. Results: The most common age group showing AUB lies under 35-40 years (40.2%) and 40-45 years (33.7%). Menorrhagia was found to be the most common symptom (66.2%). As per PALM COEIN classification, the most common type in our study was of AUB-L (33.7%) and the associated histopathological pattern was of secretory type (50.4%). Conclusions: The features and patterns of AUB differ according to the age of patient, affecting mostly women in perimenopausal and late reproductive age group. There are various modalities for its diagnosis and management and PALM COEIN classification helps better understand the disease etiology.